Cross-cultural perspectives on postpartum care: A study of Vietnamese immigrant women in South Korea - Choi, Na Youn; Kim, Young Jin (Edelweiss Applied Science and Technology, 2025)
This research investigates the postpartum care traditions of Vietnamese women who have migrated to Korea through marriage. The study was conducted in various small to medium-sized cities within the metropolitan areas of South Korea, including locations such as Gumi-si, Gyeongsangbuk-do, where a significant number of Vietnamese immigrants reside. The participants, 15 Vietnamese immigrant women, ranged in age from 20 to 31, with an average age of 25.7. They had lived in Korea for an average of 3.8 years and had all given birth within the last year. Leininger’s Sunrise Model was utilized as the analytical framework to explore and comprehend the socio-cultural context of these women's postnatal care practices. This model guided the data analysis, helping to uncover the cultural and social structures influencing their postpartum care behaviors. The research identified key principles of postpartum care among the participants, such as maintaining thermal equilibrium, warding off negative energy, detoxification, upholding hygiene, and conserving and augmenting energy. These practices were further classified into categories of ‘compliance,’ ‘adherence,’ and ‘integration,’ illustrating the women's adaptive strategies in the face of cultural differences and resource limitations. The study emphasizes the need for culturally sensitive postpartum care programs that incorporate the unique practices of Vietnamese immigrant women, providing critical insights into enhancing the quality of postpartum care and health promotion for this demographic.